Effect of contrast agent administration on water equivalent diameter in CT. Issue 3 (11th February 2021) - Viggiano, Benjamin; Rose, Sean; Szczykutowicz, Timothy P.
Abstract : Purpose: Water equivalent diameter (WED) is the preferred surrogate for patient size in computed tomography (CT). It is better than geometric size surrogates and patient weight/height/BMI/age because it correlates the best with x‐ray attenuation. The administration of oral/IV contrast agents increases a patient's attenuation and should therefore increase WED. Here we study the clinically relevant effect of oral and IV contrast agent on WED. Methods: We pulled 1703 routine adult abdominal/pelvis cases acquired at 100, 120, and 140 kV from our PACS under retrospective IRB approval. One hundred and forty cases cases had no oral or IV contrast (NONCON), 285 had just IV contrast (IV), 107 had just oral contrast (ORAL), and 1171 had both oral and IV contrast (BOTH). For each case, we measured the water equivalent and effective diameter (ED) from axial CT images. We plotted the WED versus the ED for each class of contrast. We used a linear regression model and omnibus F‐test to determine if significant differences between WED distributions existed between the contrast groups for each kV. We then performed a post hoc analysis to determine if any significant differences existed in pairwise comparisons of the different contrast groups. Bonferroni correction was used to account for multiple comparisons. Results: We found statistically significant changes at 100 and 120 kV with a maximum change of 2.1 mm. We measured a ~25 mm spread (i.e., prediction interval) of WEDs within all four contrast groups. Conclusions: While our sample size was large enough to detect statistically significant differences between some of the contrast groups, the differences were clinically irrelevant when one considers that the change in size‐specific dose estimate (SSDE) caused by our observations is roughly 1%.